Comparison of safety and efficacy of laparoscopic pyelolithotomy versus percutaneous nephrolithotomy in patients with large renal pelvic stones: a meta-analysis. Issue 6 (August 2016) - Rui, Xuefang; Hu, Haiyi; Yu, Yanlan; Yu, Shicheng; Zhang, Zhigen
Abstract : To compare percutaneous nephrolithotomy (PCNL) and laparoscopic pyelolithotomy (LP) for surgical management for large (>2 cm) renal stones. We searched MEDLINE, Cochrane, and EMBASE databases until March 11, 2015, using the following search terms: renalpelvic stone, percutaneous nephrolithotomy, laparoscopic pyelolithotomy. Randomized controlled and prospective and retrospective two-armed studies were included. Sensitivity analysis and assessment of the quality of the included studies and publication bias were performed. Nine studies were included in the study with a patient population of 622. The studies were homogeneous with respect to the primary end point of stone-free rate, but were heterogeneous with respect to operation time, length of hospital stay, and blood loss. A higher percentage of patients who received LP remained stone-free following surgery compared with patients who were treated with PCNL (p=0.001). However, the mean operation time was longer for patients with LP than for those treated with PCNL (p=0.002). There was no difference between procedures with regard to length of hospital stay or blood loss (p≥0.071). Sensitivity and quality analysis indicated that the data are reliable and the included studies are of good quality. No publication bias was observed. The study suggests that both procedures are effective and safe for removing large renal stones. However, LP may be more efficacious than PCNL in treating large kidney stones.